A fork in the road: factors contributing to elite hockey players' decisions to choose the NCAA route. Issue 7 (2nd July 2020) - Madsen, Rachel; Smith, Jimmy; Edwards, Jonathon; Gentile, Michael; Wayne, Alexis
Abstract: Elite hockey players in North America face a unique developmental pathway where there are two legitimate avenues to compete: the National Collegiate Athletics Association and Canadian Hockey League. The challenge for these athletes is to determine which is the best option at a young age (15–16 years old). This study used rational decision-making theory as means of the analyzing interviews with elite male hockey players from National Collegiate Athletic Association Division I institutions regarding why they chose these programmes as opposed to playing in the CHL. Results indicated that athletes were logical in their decision making and attempted to minimize risk as much as possible. Additional themes were identified including the influence of others (i.e. teammates, coaches) and an honest evaluation of one's strengths and weaknesses. Results of this study can provide insight into the decision-making process of elite athletes, and can contribute to successful recruiting of high-level athletes in all sports.